(untitled) (Journal of Mathematical Study, 2015)
In this paper, we derive second order estimates for a class of non-concave Hessian type elliptic equations on Riemannian manifolds. By applying a new method for C^2 estimates, we can weaken some conditions, which works for some non-concave equations. Gradient estimates are also obtained.